The CP stent—short, long, covered—for the treatment of aortic coarctation, stenosis of pulmonary arteries and caval veins, and Fontan anastomosis in children and adults: an evaluation of 60 stents in 53 patients. Issue 7 (14th June 2005) - Ewert, P; Schubert, S; Peters, B; Abdul-Khaliq, H; Nagdyman, N; Lange, P E
Abstract : Objective: To evaluate the feasibility and usefulness of the Cheatham platinum (CP) stent in a broad spectrum of lesions. Methods: Retrospective analysis of 60 implanted CP stents (11–80 mm lengths, 12 covered) between September 2001 and March 2004. Patients: 53 patients aged 2.5–68 years (median 17 years). Body weight ranged from 12–95 kg (median 52 kg). Thirty six patients had aortic (re)coarctation; seven of them had functionally interrupted aortic arches. Thirteen patients had pulmonary artery stenosis and four had stenosis of caval veins or conduits in a total cavopulmonary connection (TCPC). Results: Arterial pressure gradients dropped from 33 mm Hg (range 20–80 mm Hg) to 5 mm Hg (range 0–10 mm Hg) and pressure gradients in TCPC or caval veins dropped from 4 mm Hg (range 4–20 mm Hg) to 0 mm Hg (range 0–3 mm Hg). All stents were placed in the target lesion without complications. Three stent fractures without clinical instability were noted. Conclusions: The CP stent is suitable for the treatment of vessel stenosis in congenital heart diseases from childhood to adulthood. Whether these good results will be stable in the long term needs to be investigated.